Accuracy of Various Forms of Contrast-Enhanced MRI for Diagnosing Hepatocellular Carcinoma: A Systematic Review and Meta-Analysis - Zhao, Chun; Dai, Hongyan; Shao, Juwei; He, Qian; Su, Wei; Wang, Peng; Tang, Qiuyue; Zeng, Junren; Xu, Song; Zhao, Juanjuan; Xiang, Shutian (Frontiers in Oncology, 2021)
BACKGROUND: Contrast-enhanced MRI can be used to identify patients with hepatocellular carcinoma (HCC). However, studies around the world have found differing diagnostic accuracies for the technique. Hence, we designed this meta-analysis to assess the accuracy of contrast-enhanced MRI for HCC diagnosis. METHODS: We conducted a systematic search for all studies reporting the diagnostic accuracy of contrast-enhanced MRI for HCC in the databases of MEDLINE, EMBASE, Cochrane library, Web of Science, SCOPUS, ScienceDirect, and Google Scholar from inception until January 2021. We used the “Midas” package from the STATA software to perform the meta-analysis. RESULTS: Our study was based on 21 publications with 5361 patients. The pooled HCC diagnosis sensitivity and specificity were 75% (95% CI, 70%-80%) and 90% (95% CI, 88%-92%), respectively, for gadoxetic acid-enhanced MRI; and, they were 70% (95% CI, 57%-81%) and 94% (95% CI, 85%-97%), respectively, for ECA-MRI. We found significant heterogeneity with a significant chi-square test and an I2 statistic > 75%. We also found significant publication bias as per the Deek’s test results and funnel plot. CONCLUSION: We found that both types of contrast-enhanced MRI are accurate diagnostic and surveillance tools for HCC and offer high sensitivity and specificity. Further studies on different ethnic populations are required to strengthen our findings.